High connectivity in the deepwater snapper Pristipomoides filamentosus (lutjanidae) across the indo-pacific with isolation of the Hawaiian archipelago - Gaither, M.; Jones, S.; Kelley, C.; Newman, Stephen; Sorenson, L.; Bowen, B. (Public Library of Science, 2011)
In the tropical Indo-Pacific, most phylogeographic studies have focused on the shallow-water taxa that inhabit reefs to approximately 30 m depth. Little is known about the large predatory fishes, primarily snappers (subfamily Etelinae) and groupers (subfamily Epinephelinae) that occur at 100-400 m. These long-lived, slow-growing species support fisheries across the Indo-Pacific, yet no comprehensive genetic surveys within this group have been conducted. Here we contribute the first range-wide survey of a deepwater Indo-Pacific snapper, Pristipomoides filamentosus, with special focus on Hawai'i. We applied mtDNA cytochrome b and 11 microsatellite loci to 26 samples (N = 1,222) collected across 17,000 km from Hawai'i to the western Indian Ocean. Results indicate that P. filamentosus is a highly dispersive species with low but significant population structure (mtDNA F ST = 0.029, microsatellite F ST = 0.029) due entirely to the isolation of Hawai'i. No population structure was detected across 14,000 km of the Indo-Pacific from Tonga in the Central Pacific to the Seychelles in the western Indian Ocean, a pattern rarely observed in reef species. Despite a long pelagic phase (60-180 days), interisland dispersal as adults, and extensive gene flow across the Indo-Pacific, P. filamentosus is unable to maintain population connectivity with Hawai'i. Coalescent analyses indicate that P. filamentosus may have colonized Hawai'i 26 K-52 K y ago against prevailing currents, with dispersal away from Hawai'i dominating migration estimates. P. filamentosus harbors low genetic diversity in Hawai'i, a common pattern in marine fishes, and our data indicate a single archipelago-wide stock. However, like the Hawaiian Grouper, Hyporthodus quernus, this snapper had several significant pairwise comparisons (F ST) clustered around the middle of the archipelago (St. Rogatien, Brooks Banks, Gardner) indicating that this region may be isolated or (more likely) receives input from Johnston Atoll to the south. © 2011 Gaither et al.